Students’ Problems in Building up English Vocabulary (Scripta : English Department Journal, 2023)
The aims of the research were to analyze the students’ problems in building up English vocabulary and the alternative solutions to overcome students problems in building up English vocabulary during COVID-19 pandemic at the eighth grade of SMP Negeri 3 Kepil by using descriptive analysis methods. To select the participants, the researcher chose VIII/A, which consisted of 32 students to answer the questionnaire. Besides, the researcher chose an English teacher to answer the interview. In this research there were three processes for analyzing data, including: data condensation, data display, and drawing conclusion. Finally, the result of students’ problems were: 1) having low motivation (81%) having low interest (75%), 2) lazy in memorizing English words (84%), 3) did not understand the grammar (91%) and did not understand the meaning of words in English (84%), 4) did not understand the English pronunciation (91%), 5) have no sufficient learning facilities (internet connection) (97%). Then, the alternative solutions were: 1) using a dictionary (84%), 2) learning with friends (78%), 3) making a note (68%), 4) searching in the internet (59%), 5) listening to English music (75%). From the results, it could be concluded that the main problem for students in building English vocabulary in the COVID-19 pandemic situation was that they had problem in the learning facility in the form of bad internet connection with a percentage of the problem was (97%). Besides, the main alternative solution to overcome students’ problems was using a dictionary with a percentage was (84%).
Keywords: Building up English vocabulary; Students’ problems; COVID-19 pandemic